Pengaruh durasi waktu pengelasan pada proses las gesek terhadap sifat mekanik material AISI 1045 - Andi Suhendar; Mawardi Mawardi; Akhyar Ibrahim (Politeknik Negeri Lhokseumawe, 2020)
Welding is an important process in the industrial world and is an integral part of industrial growth. One type of welding that exists today is friction welding. Friction welding technology is a method of solid state welding where the heat source is generated by two metals rubbing together without any added metal. The purpose of this research is to determine the effect of welding time on the mechanical properties of the AISI 1045 material. The method used is to combine heat and pressure without the two metals being properly connected. Next, vary the welding time for 1 minute, 1.5 minutes, and 2 minutes with a rotation of 2500 rpm. After performing friction welding, each specimen will be subjected to a tensile test. From the research data shows that the friction welding process using 1 minute has the highest tensile strength value, namely 709.44 Mpa, then followed by 1.5 minutes, namely 439.64 Mpa, and then followed by 2 minutes, namely 145 79 Mpa. And then for the average hardness value at 1 minute is 74.20 HRC in the stir zone area, then for 1.5 minutes the average hardness value is 68.90 HRC in the stir zone area. Meanwhile, in 2 minutes, the Rockwell hardness value was 67.00 HRC. From the results of the research data, it can be concluded that the magnitude of the rotation and welding time affect the mechanical properties of the welding results